2019
DOI: 10.17508/cjfst.2019.11.1.03
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of nutritional composition and functional and pasting properties of wheat flour-coconut flour blends

Abstract: The feasibility of partially replacing wheat flour with coconut flour in baked products was investigated. Matured coconut (Cocos nucifera) endocarp was grated for the extraction of milk, dried, milled,and pulverized. Five blends of composite flour were prepared by combining wheat flour with 10% to 50% of partially defatted coconut flour,respectively. The 100% wheat flour served as control. The samples were analysed for proximate, mineral, functional,and pasting properties using standard procedures. The proxima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…The DCF 0% had lower calcium content compared to the other samples, and this is due to the high calcium content of DCF (Trinidad et al ., 2006). Makinde & Eyitayo (2019) reported that an increase in DCF increased the calcium content in the wheat and coconut flour blends. Generally, foods with protein are a rich source of zinc (Chong, 1997).…”
Section: Resultsmentioning
confidence: 99%
“…The DCF 0% had lower calcium content compared to the other samples, and this is due to the high calcium content of DCF (Trinidad et al ., 2006). Makinde & Eyitayo (2019) reported that an increase in DCF increased the calcium content in the wheat and coconut flour blends. Generally, foods with protein are a rich source of zinc (Chong, 1997).…”
Section: Resultsmentioning
confidence: 99%
“…It was revealed that sample BTT (70 % wheat flour + 15 % AYB flour + 15 % tigernut flour) had the lowest value which implies that it will be a more stable gel during cooking. Makinde & Eyitayo [ 65 ] reported trough ranged from 750.5 to 964.0 RVU for wheat coconut flour blends. Breakdown viscosity is an index of the stability to rupture swollen starch granules when held at high temperatures with continuous shearing [ 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is dried and degreased to obtain a fine powder. Coconut is considered a nutraceutical food because of its many health benefits [11][12][13].…”
Section: Introductionmentioning
confidence: 99%